Transients by Black Hole Formation from Red Supergiants: Impact of Dense Circumstellar Matter - Daichi Tsuna; Xiaoshan Huang; Jim Fuller; Anthony L. Piro (The Astrophysical Journal)
Failed supernovae (SNe), which are likely the main channel for forming stellar-mass black holes, are predicted to accompany mass ejections much weaker than typical core-collapse SNe. We conduct a grid of one-dimensional radiation hydrodynamical simulations to explore the emission of failed SNe from red supergiant progenitors, leveraging recent understanding of the weak explosion and the dense circumstellar matter (CSM) surrounding these stars. We find from these simulations and semianalytical modeling that diffusion in the CSM prolongs the early emission powered by shock breakout/cooling. The early emission has peak luminosities of ~10 ^7 –10 ^8 L _⊙ in optical and UV and durations of days to weeks. The presence of dense CSM aids in the detection of the early bright peak from these events via near-future wide-field surveys such as Rubin Observatory, ULTRASAT, and UVEX.